2021
DOI: 10.1103/physrevb.104.115120
|View full text |Cite
|
Sign up to set email alerts
|

Optical response and band structure of LiCoO2 including electron-hole interaction effects

Abstract: The optical response functions and band structures of LiCoO 2 are studied at different levels of approximation, from density functional theory (DFT) in the generalized gradient approximation (GGA) to quasiparticle selfconsistent QSGW (with G for Green's function and W for screened Coulomb interaction) without and with ladder diagrams (QSG Ŵ ) and the Bethe Salpeter Equation (BSE) approach. The QSGW method is found to strongly overestimate the band gap and electron-hole or excitonic effects are found to be impo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
5
19
0
Order By: Relevance
“…This strong renormalization of the low-energy excitations and lack of a band-like absorption onset rules out standard spectrum fitting techniques (such as the Tauc and Elliott models) for extracting band gap and exciton binding energies. 53,54 Notably, the experimental spectra for TiBr 6 2and TiCl 6 2salts reported in Brisdon et al 55 closely resemble the results for Cs 2 TiBr 6 and Cs 2 TiCl 6 reported here and in the literature, 36,37 evidencing the conclusion of molecular crystal behavior, the orbital assignments of the absorption peaks and the presence of strong electron-hole interactions. Improved agreement between the calculated and experimental spectra is also found for the Sn compounds upon inclusion of electron-hole interactions, as weaker exciton interactions modify transition intensities and shift spectral weights to give more peak-like absorption onsets.…”
Section: Resultssupporting
confidence: 86%
“…This strong renormalization of the low-energy excitations and lack of a band-like absorption onset rules out standard spectrum fitting techniques (such as the Tauc and Elliott models) for extracting band gap and exciton binding energies. 53,54 Notably, the experimental spectra for TiBr 6 2and TiCl 6 2salts reported in Brisdon et al 55 closely resemble the results for Cs 2 TiBr 6 and Cs 2 TiCl 6 reported here and in the literature, 36,37 evidencing the conclusion of molecular crystal behavior, the orbital assignments of the absorption peaks and the presence of strong electron-hole interactions. Improved agreement between the calculated and experimental spectra is also found for the Sn compounds upon inclusion of electron-hole interactions, as weaker exciton interactions modify transition intensities and shift spectral weights to give more peak-like absorption onsets.…”
Section: Resultssupporting
confidence: 86%
“…12). Further details of this recent work can be found in Radha et al [140] This clearly shows that in LiCoO 2 the optical absorption onset corresponds to strong Frenkel excitons and is significantly different from the quasiparticle gap. The exciton binding energy is of order 2.3 eV.…”
Section: D Effects On Electronic Structurementioning
confidence: 75%
“…As it is shown in this study, combining the vertex corrected calculations with QP self-consistency as it is advocated in Refs. [13][14][15], can only be successful if vertex corrections are evaluated with a number of restrictive approximations or 'constraints' such as polarizability only correction, static W (ν = 0) in vertex diagrams, and Tamm-Dancoff approximation when solving BSE. From this point of view, quasi-particle self-consistency combined with vertex-corrected GW approach can be considered as an ad hoc theory where one imposes specific constraints on the vertex part in order to avoid too large (and destructive for the final result) effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to the approach used in Refs. [13][14][15], our implementation of QSGW+DMFT also uses 'constraints' for the vertex (DMFT) part: i) only one iteration which includes DMFT (one-shot type of DMFT correction performed on top of QSGW); ii) effective interaction in DMFT part is not evaluated from proper DMFT self-consistency condition, [50], but is provided by constrained random-phase approximation (cRPA, [51]). Specifically, the second constraint (using the cRPA) can clearly be considered as an ad hoc part where the setup parameters of cRPA are adjusted in order to get reasonable effective interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation